Encountering the sacred : the debate on Christian pilgrimage in late antiquity - Bitton-Ashkelony, Bruria (Berkeley : University of California Press, 2005)
This innovative study sheds new light on one of the most spectacular changes to occur in late antiquity--the rise of pilgrimage all over the Christian world--by setting the phenomenon against the wide background of the political and theological debates of the time.
Preface; Abbreviations; Introduction: Pilgrimage in Late Antiquity; 1. Basil of Caesarea's and Gregory of Nyssa's Attitudes Toward Pilgrimage; 2. Jerome's Position on Pilgrimage: Vacillating Between Support and Reservations; 3. Augustine on Holy Space; 4. Pilgrimage in Monastic Culture; 5. Local Versus Central Pilgrimage; Bibliography; General Index; Index of Places; Index of Biblical Citations.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Christian pilgrims and pilgrimages -- Palestine -- History of doctrines -- Early church, ca. 30-600.; Palestine -- In Christianity -- History of doctrines -- Early church, ca. 30-600.; RELIGION -- Holidays -- Christian; RELIGION -- Antiquities & Archaeology; Middle East -- Palestine; 30 - 600